Implementasi Undang-Undang Ketenagakerjaan dalam Kasus PHK - Reiska Indah Ayu Wulandari; Romi Faslah (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Termination of Employment (Pemutusan Hubungan Kerja or PHK) is still an important issue in industrial relations in Indonesia, which is regulated by labor law to ensure fairness and protection for both employers and employees. Ideally, layoffs should be the last resort after proper procedures and mutual agreement. This article analyzes the legal framework of layoffs, its types, and worker protection under Law No. 13 Year 2003 and related regulations. Using normative and empirical juridical methods, the study includes an analysis of the case of PT Sritex, which experienced bankruptcy and resulted in mass layoffs. The research findings show that there are ongoing legal violations in the implementation of layoffs that have negative psychological, social, and economic impacts on workers. Structural weaknesses, limited law enforcement, and unequal power dynamics between employers and workers further exacerbate the situation. To overcome these challenges, stronger legal supervision and active cooperation between the government, employers, and workers are needed to promote a fair, balanced, and sustainable labor environment.